An authentic record of Eutropis bibronii (Gray, 1838) (Reptilia: Scincidae) from Sri Lanka - Silva, Anslem De; Sandaruwan, W. M. J.; Zoysa, H. K. Sameera De; Ukuwela, Kanishka D.b. (Zootaxa, 2017)
Among the eight species of Eutropis Fitzinger currently known from Sri Lanka, Eutropis bibronii (Gray, 1838) is among the least known. Hence, the occurrence of this species in Sri Lanka has been doubted by some authors since there were no confirmed records from live specimens for the past 70 years. The species has been previously reported mostly from northern regions of Sri Lanka. Here, we report the collection of a live Eutropis bibronii from the Chundikulam National Park in the Northern Province of Sri Lanka confirming its occurrence in the country.